2011
DOI: 10.1177/1046496410397381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anonymity and Social Comparison of Rewards on Computer-Mediated Group Brainstorming

Abstract: Anonymity in computer-mediated communication (CMC) is valued in organizations because it can facilitate participation in discussions, especially of sensitive issues. Concerns over maintaining the motivation to participate in such discussions, because of the inability to reward people for their contributions, have led to the development of techniques that allow rewards to be allocated without identifying their distributors and recipients. It was hypothesized, however, that anonymous rewards are not equivalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 92 publications
0
10
0
2
Order By: Relevance
“…Researchers have also examined whether social loafing could be reduced in virtual teams by identifying individual contributions. Pissarra and Jesuino [32] found no significant reduction in social loafing due to the identification of individual contributions; while McLeod [33] did but only when individuals engaged in social comparisons. Finally, this work has been complemented by Suleiman and Watson [24] which found that individual self-feedback reduced social loafing.…”
Section: Social Loafing In Virtual Teamsmentioning
confidence: 92%
“…Researchers have also examined whether social loafing could be reduced in virtual teams by identifying individual contributions. Pissarra and Jesuino [32] found no significant reduction in social loafing due to the identification of individual contributions; while McLeod [33] did but only when individuals engaged in social comparisons. Finally, this work has been complemented by Suleiman and Watson [24] which found that individual self-feedback reduced social loafing.…”
Section: Social Loafing In Virtual Teamsmentioning
confidence: 92%
“…As representações positivas dos novos média ainda incidem sobre a forma como podem ser utilizados para proteger o direito das pessoas à comunicação privada e ao acesso à informação (Floridi, 2014;Hoang & Pishva, 2014;Jardine, 2018;McLeod, 2011;Sharon & John, 2018;Wu & Atkin, 2018). No entanto, novas e crescentes formas de crime e violência através dos novos média ilustram em que medida o desenvolvimento tecnológico acrescenta sofisticação ao cibercrime, promovendo visões e representações mais céticas da internet (Larsson et al, 2012;Martin, 2014;Morselli et al, 2017;van Hardeveld et al, 2017).…”
Section: Os Novos Média Como Plataforma Para a Violência E O Crimeunclassified
“…We introduce "status anonymity" as a potentially positive constraint in the creative process. Research on the positive effects of anonymity in electronic brainstorming sessions is extensive (Cooper et al, 1998;McLeod, 2011;Sosik et al, 1998). However, research that investigates the effect of anonymity in face-to-face activities, such as workshops or co-creation, is scarce.…”
Section: Anonymity In the Creative Processmentioning
confidence: 99%